THE USE OF STORY FACE STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION THROUGH A DEEP LEARNING APPROACH IN TEACHING NARRATIVE TEXT AT SMKN 1 SITIUNG - Jantika Sabrina; Riyadi Saputra; Norasiah (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Reading comprehension is an essential skill in English language learning, particularly in understanding narrative texts. However, many students experience difficulties in identifying main ideas, understanding sequences of events, and comprehending texts. This study aimed to examine the effect of implementing the Story Face Strategy through a Deep Learning approach on students' reading comprehension of narrative texts. A quantitative pre-experimental design with a one-group pre-test and post-test was employed. The participants were 20 eleventh-grade students of the Computer and Network Engineering (TKJ) program at SMKN 1 Sitiung, selected through purposive sampling. The research instrument was a reading comprehension test consisting of multiple-choice and essay questions that had been tested for validity and reliability. Data were analyzed using the Shapiro–Wilk test, Paired Samples t-test, and Normalized Gain (N-Gain) test. The findings revealed a significant improvement in students' reading comprehension, with the mean score increasing from 51.30 in the pre-test to 80.95 in the post-test (p < .001). The N-Gain score of 0.6136 indicated a moderate level of improvement. These findings suggest that the Story Face Strategy integrated with the Deep Learning approach is effective in improving students' reading comprehension of narrative texts.